Development of the Silindar E-Module Based on Problem Based Learning with a STEM Approach on SPLDV to Enhance Students Problem Solving Skills - Muhammad Farkhan Tamam; Iswahyudi Joko Suprayitno; Eko Andy Purnomo (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Mathematics learning in schools should be able to optimally stimulate these higher-order thinking skills to meet the demands of 21st-century competencies. However, conditions in the field show that learning still tends to be teacher-centered and the availability of contextual teaching materials is limited. This condition triggers students' difficulties in formulating mathematical models, especially in the SPLDV material, so that students' problem-solving abilities are not optimally honed. This development research is specifically limited to the objective of developing and testing the level of validity and practicality of the Silindar E-Module on SPLDV material based on Problem Based Learning (PBL) and the STEM approach. The method used is development research with the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. Data collection uses validation sheets from media experts and material experts, as well as questionnaire responses from teachers and students. The results of the study show that the Silindar E-module meets the criteria of being very valid in terms of design and material substance with an average overall validity score of 3.68 consisting of a media expert assessment of 3.76 and a material expert assessment of 3.60. The Silindar E-module was also declared very practical when applied in learning based on an average combined practicality of 3.56 with the results of the teacher response questionnaire with an average of 3.73 and a student response of 3.39. These findings confirm that the Silindar E-module is suitable for use as an interactive learning tool to facilitate the improvement of students' mathematical problem-solving abilities and support the implementation of the independent curriculum.